2015
DOI: 10.1038/onc.2015.40
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear heparanase-1 activity suppresses melanoma progression via its DNA-binding affinity

Abstract: Heparanase-1 (HPSE) plays a pivotal role in structural remodeling of the ECM and glycocalyx thus conferring protumorigenic, proangiogenic and prometastatic properties to many cancer entities. In addition to its extracellular function, recent studies suggest an intracellular activity of HPSE with a largely unknown significance during tumor progression. Therefore, we investigated the relevance of HPSE duality in malignant melanoma in vitro as well as in mouse melanoma models basing on the intradermal injection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 58 publications
2
44
0
Order By: Relevance
“…A corresponding decrease in nuclear heparan sulfate further confirms this observation (Figure 4C). Bearing in mind previous suggestions of the ability of HPSE to localize to the nucleus (Schubert et al, 2004; Nobuhisa et al, 2007), bind to DNA (Yang et al, 2015), and regulate chromatin modifications (He et al, 2012; Hong et al, 2012), we hypothesized that HPSE influences cytokine signaling by interaction with transcription factors. Indeed, western blot analysis of nuclear and cytoplasmic extracts from HCE cells (Figure 4D,E) and HeLa cells (Figure S3D) overexpressing GS3-HPSE showed significantly enhanced translocation of nuclear factor (NF)-κB to the nucleus upon infection.…”
Section: Resultsmentioning
confidence: 99%
“…A corresponding decrease in nuclear heparan sulfate further confirms this observation (Figure 4C). Bearing in mind previous suggestions of the ability of HPSE to localize to the nucleus (Schubert et al, 2004; Nobuhisa et al, 2007), bind to DNA (Yang et al, 2015), and regulate chromatin modifications (He et al, 2012; Hong et al, 2012), we hypothesized that HPSE influences cytokine signaling by interaction with transcription factors. Indeed, western blot analysis of nuclear and cytoplasmic extracts from HCE cells (Figure 4D,E) and HeLa cells (Figure S3D) overexpressing GS3-HPSE showed significantly enhanced translocation of nuclear factor (NF)-κB to the nucleus upon infection.…”
Section: Resultsmentioning
confidence: 99%
“…Heparanase can also interfere with gene transcription directly by binding to nuclear DNA or indirectly by controlling histone H3 methylation patterns . The overexpression of heparanase in melanoma cell lines prompted us to study its role on cancer cells per se . Accordingly, melanoma MDA‐MB‐435s cells and MV3 cells expressed remarkably high levels of endogenous heparanase (Figure A).…”
Section: Discussionmentioning
confidence: 99%
“…HS is a glycosaminoglycan (GAG) that is present in almost all mammalian tissues on cell surfaces and in the extracellular matrix (17,26,27). It plays a key role in ECM integrity, barrier function, and cell-ECM interactions and is used by many viruses for initial attachment to target cells.…”
Section: Discussionmentioning
confidence: 99%
“…HS is present in almost all mammalian tissues and plays a key role in ECM integrity, barrier function, and cell-ECM interactions (16). As the only known enzyme capable of degrading HS at specific intrachain sites, heparanase (HPSE) mediates the release of HS-bound cytokines, growth factors, lipoproteins, enzymes, and viruses (17). Previous studies have shown that HS expression is increased during the initial stage of herpes simplex virus 1 (HSV-1) infection to enhance viral attachment to cells.…”
mentioning
confidence: 99%